2018
DOI: 10.1016/j.jstrokecerebrovasdis.2017.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Outcomes after Stroke in Patients with Diabetes in Ontario, Canada

Abstract: In this large, population-based, retrospective study among diabetic patients with index stroke, women had a higher unadjusted death rate but lower unadjusted incidence of MI. In adjusted models, females had a lower death rate compared with males, although the increased risk of MI among males persisted. These findings confirm and quantify sex differences in outcomes after stroke in patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 34 publications
(57 reference statements)
2
25
0
Order By: Relevance
“…Our results differ from a German IS study that found no DM-related mortality differences for women but diabetic men with IS had lower short-term mortality, compared with non-diabetic men; notably, this effect did not persist after a year ( 16 ). A recent Canadian study showed lower mortality in DM women ( 17 ). However, neither study adjusted for stroke severity and disability previous to the index stroke.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our results differ from a German IS study that found no DM-related mortality differences for women but diabetic men with IS had lower short-term mortality, compared with non-diabetic men; notably, this effect did not persist after a year ( 16 ). A recent Canadian study showed lower mortality in DM women ( 17 ). However, neither study adjusted for stroke severity and disability previous to the index stroke.…”
Section: Discussionmentioning
confidence: 98%
“…A recent meta-analysis has estimated that women with DM have a 27% greater risk of stroke than men with DM ( 10 ), and some studies suggest that they have worse survival and functional outcome than men ( 11 14 ). Other studies, however, have found increased mortality for both women and men with diabetes ( 15 ), a time-dependent mortality risk only for DM men ( 16 ), and lower adjusted mortality in DM women than in men ( 17 ) The reasons for these sex differences are unknown, and the majority of the research has focused on comparing men and women with DM, with little information about how sex can influence the short- and long-term impact of DM on post-IS prognosis. On the other hand, many of these studies are unadjusted ( 12 , 17 ) or adjusted only by age and vascular risk factors ( 14 17 ) or previous treatments ( 15 , 16 ) without taking into account two of the most important predictors of mortality: previous disability and stroke severity.…”
Section: Introductionmentioning
confidence: 95%
“…Nevertheless, women with diabetes had a higher risk of AKI than men. Previous studies have yielded equivocal results regarding the interaction between sex and diabetes mellitus in stroke outcomes, which could be due to ethnic differences between populations [21][22][23]. More research is needed to clearly establish the relationship between diabetes, sex and stroke outcomes in different populations.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that the type of stroke did not lead to a worse 1 and 5 year survival for those who survived the first 28 days after the stroke, although having assessed all cases of stroke, we noticed that the hemorrhagic and subarachnoid type of stroke significantly led to higher mortality. It can be argued that long-term survival was more influenced not by clinical signs or complications, but by chronic concomitant illness, bad control of stroke risk factors or harmful lifestyle [43, 46, 47].…”
Section: Discussionmentioning
confidence: 99%